Perbedaan Faktor Yang Mempengaruhi Minat Berwirausaha Mahasiswa Universitas Teknologi Sumbawa Dengan Mahasiswa STIE Bima - Hermanto, Koko; Muniarty, Puji; Permata, Dinda; Ananda, Dea; Fitriani, Reza; Atira, Fatin Farah; Nurfadila, Nurfadila; Ningsih, Nur Fitria (Jurnal Ilmiah Global Education, 2024)
Currently, the number of unemployed in West Nusa Tenggara province is dominated by university graduates. One effort to reduce unemployment is to become an entrepreneur. In every tertiary institution, including the Sumbawa University of Technology (UTS) and Sekolah Tinggi Ilmu Ekonomi (STIE) Bima, there are entrepreneurship courses, which can later make students become drivers in developing a business spirit to become entrepreneurs. Therefore, this research aims to determine the influence of entrepreneurship courses and family support on the entrepreneurial interest of UTS and STIE Bima students using the structural equation model (SEM) method. The research results show that the entrepreneurship course material significantly affects UTS students' entrepreneurial intentions. Meanwhile, STIE Bima students' entrepreneurial intentions are influenced not only by the entrepreneurship course material but also by the delivery of the course material.